Determination of Aflatoxin B1 Levels in Organic Spices and Herbs - Halil Tosun; Recep Arslan (The Scientific World Journal)
Organically produced spices and herbs were analyzed for determination of aflatoxin B1 (AFB1) by ELISA using immunoaffinity column. For this purpose 93 organic spices and 37 organic herbs were randomly selected from organic markets and organic shops in Turkey. AFB1 was detected in 58 organic spice and 32 organic herb samples. Among organic spice samples, the maximum value was detected in cinnamon sample (53 μg/kg). AFB1 was not detected in thyme samples. AFB1 levels of 41 organic spice samples were above the EU regulatory limit (5 μg/kg). Among organic herb samples the highest concentration of AFB1 (52.5 μg/kg) was detected in a rosehip sample. AFB1 levels of 21 organic herb samples were above the regulatory limits of the European Union. These results showed that more stringent measures must be taken for the prevention of mold contamination in the production of organic spices and herbs.